Technology-Based Digitalization of Islamic Religious Education: Digitalisasi Pembelajaran Pendidikan Agama Islam Berbasis Teknologi - Suaidi, Suaidi; Faridi, Faridi; Sunarto, Sunarto (Halaqa: Islamic Education Journal, 2025)
This study aims to analyze the implementation of digitalization in Islamic Religious Education (PAI) learning at SMA Muhammadiyah 9 Brondong within the context of educational transformation in the era of the Industrial Revolution 4.0 and the post-pandemic period. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and document analysis. The findings indicate that the school has adopted various digital platforms and online learning applications to support PAI instruction. The main challenges include limited infrastructure, low digital literacy among teachers and students, and unequal internet access. A distinctive finding of this study is the integration of Islamic values into digital media, which not only enhances religious understanding but also contributes to character formation in virtual learning environments. The theoretical contribution of this research lies in mapping a model of PAI digital learning that incorporates local wisdom and spiritual values within the framework of educational technology. Furthermore, the results show that digitalization significantly enhances learning effectiveness and student engagement. The study recommends strengthening digital infrastructure, providing continuous training for educators, and developing an adaptive and contextual digital-based PAI curriculum as a long-term development strategy. Highlights: Integration of Islamic values into digital learning. Addressing infrastructure and digital literacy gaps. Enhancing engagement through technology-based PAI learning. Keywords: Digitalization, Islamic Religious Education, Online Learning, Teacher Training, Student Engagement